2016
DOI: 10.18549/pharmpract.2016.04.832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the addition of acarbose to insulin and non-insulin regimens in veterans with type 2 diabetes mellitus

Abstract: Objectives:The primary objective of the study was to assess the mean change in hemoglobin A1c (HbA1c) when acarbose was added to insulin and non-insulin regimens in patients with type 2 diabetes mellitus (T2DM). Secondary objectives were to evaluate the discontinuation rate of acarbose, and to assess the number of patients who were placed on insulin despite the addition of acarbose.Methods:A retrospective chart review was conducted on veterans with T2DM initiated on acarbose between October 1, 2013 and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…GDs are the main side effects of acarbose. In our study, the incidence of GDs in the acarbose group (24.6%) was similar to that in previous reports (5,21,22,28,29,31,32,35). The incidence of GDs in the SZ-A group was 12.2%, which was much lower than the acarbose group, showing a significant difference.…”
Section: Carediabetesjournalsorgsupporting
confidence: 90%
See 1 more Smart Citation
“…GDs are the main side effects of acarbose. In our study, the incidence of GDs in the acarbose group (24.6%) was similar to that in previous reports (5,21,22,28,29,31,32,35). The incidence of GDs in the SZ-A group was 12.2%, which was much lower than the acarbose group, showing a significant difference.…”
Section: Carediabetesjournalsorgsupporting
confidence: 90%
“…People in East Asia usually rely on starchy foods as their main source of calories; therefore, a-glucosidase inhibitors are often used as the first-line drug for the treatment of patients with diabetes in this region (18)(19)(20). However, these drugs are associated with a high incidence of gastrointestinal disorders (GDs), such as abdominal distension, abdominal pain, and diarrhea, because of low selectivity to a-glucosidase (5,21,22). In vitro experiments have shown that SZ-A imparts a significant inhibitory effect on sucrase and maltase, which is equal to or slightly stronger than that of acarbose.…”
mentioning
confidence: 99%
“…α-Glucosidase inhibition is an established protocol for diabetes therapy, although some commercially available drugs based on carbohydrate-related structures, such as acarbose, voglibose, and miglitol have shown certain side effects . In particular, acarbose is employed as a last-line treatment for T2DM, and when this drug is administered in association with a high-carbohydrate diet, patients complain of flatulence, abdominal cramps, liver problems, lactic acidosis, nausea, and diarrhea. , Thus, there is an active search for new and effective α-glucosidase inhibitors with negligible undesirable side effects . In this context, special attention has been devoted to inhibitors of natural origin, possibly showing significant antioxidative properties.…”
mentioning
confidence: 99%
“…Acarbose is considered a last-line intervention treatment for T2DM ( 8 ). The two sugar units within the structure of the compound form the functional inhibitory site that binds to α-glucosidases in the small intestine and α-amylase in the pancreas ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The two sugar units within the structure of the compound form the functional inhibitory site that binds to α-glucosidases in the small intestine and α-amylase in the pancreas ( 9 ). Due to the mechanistic nature of acarbose, patients complained of gastrointestinal discomfort, flatulence, abdominal cramps, nausea, and diarrhea when using acarbose and consuming a high carbohydrate diet ( 8 ).…”
Section: Introductionmentioning
confidence: 99%